1989
DOI: 10.1172/jci114027
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: six gene rearrangements and an exonic point mutation in the alpha-galactosidase gene.

Abstract: Fabry disease, an X-linked recessive disorder of glycosphingolipid catabolism, results from the deficient activity of the lysosomal hydrolase, a-galactosidase. Southern hybridization analysis of the a-galactosidase gene in affected hemizygous males from 130 unrelated families with Fabry disease revealed six with different gene rearrangements and one with an exonic point mutation resulting in the obliteration of an Msp I restriction site. Five partial gene deletions were detected ranging in size from 0.4 to > 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

1990
1990
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(73 citation statements)
references
References 65 publications
1
70
0
2
Order By: Relevance
“…Bernstein et al (1989) reported that partial gene deletions were seen only seven families out of 130 families by Southern blotting analysis. They also reported a point mutation (C---,T) detected by MspI digestion of the genomic DNA PCR product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bernstein et al (1989) reported that partial gene deletions were seen only seven families out of 130 families by Southern blotting analysis. They also reported a point mutation (C---,T) detected by MspI digestion of the genomic DNA PCR product.…”
Section: Discussionmentioning
confidence: 99%
“…Since then molecular analysis of this disease has been reported. Various types of deletion of genomic DNA were found in about 5~ of patients (Bernstein et aL, 1989) and point mutations have been reported from the rest of patients (Bernstein et al, 1989;Koide et al, 1990;Sakuraba et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The COS-1 cell lines were obtained from the American Type Culture Collection (Rockville, MD). The fibroblasts, lymphoblasts, and COS-1 cell lines were grown in RPMI 1640 media supplemented with 10% fetal bovine serum, 1% penicillin, and I mg/ml streptomycin by standard procedures (10).…”
Section: Methodsmentioning
confidence: 99%
“…A severe deficiency in ~-Gal A activity results in Fabry disease, a glycosphingolipid storage disorder. Many different mutations in the et-GAL A gene have been correlated with this disease, including partial gene deletions, insertions, and a variety of single-base substitutions affecting mRNA processing or translation [7,8].…”
Section: Introductionmentioning
confidence: 99%